Rotifers rotifera monogononta - Bielańska-Grajner, Irena (Łódź University Press, 2015)
Rotifers (Rotifera) are animals which occur in every type of aquatic environment, both marine and freshwater. They owe their wide distribution to rapid reproduction. Due to their high abundances, they play an important role in freshwater ecosystems. The world's fauna includes about 2000 rotifer species, 1350 of them being reported from Europe. This book consists of two main parts. The general part includes such topics as origin of rotifers, taxonomy and systematics, morphology, anatomy, biology, ecology, zoogeography, and methods of sample collection, preservation, storage, and processing. In the systematic part the keys to orders, families and genera, and survey of species, based on illustrations including many original micrographs on colour, are put. In total, over 460 rotifer species found in Poland are presented and characterized. Additionally over 140 species which were not yet recorded from Poland but they are known to occur in the neighbouring countries, so it is possible to encounter them in Poland in the future. The text is supplemented by list of references, index of systematic names and list of synonims used in Polish literature. 'This book would be useful not only for those who specialise in rotifer research, but also for other recipients as zoologists and hydrobiologists, biology students, teachers and specialists of water quality management and protection practice.' Anna Hillbricht-llkowska